Comparative Study Of Financial Performance (Islamic VS Conventional Bank During Covid-19) - Azam Asykarulloh; Hasan Sultoni (Universitas Muhammadiyah Ponorogo, 2023)
Covid-19 has had a significant impact on the banking economic sector, both Islamic banks and conventional banks. This article attempts to reveal a comparison of the financial performance of Islamic and conventional banking as measured using the CAMELS ratio. The camels ratio component consists of aspects of capital, assets, management, earnings, liquidity and sensitivity. This component is measured by the ratio of CAR, NPL/NPF, BOPO, ROE, LDR/FDR. The method used is the difference test with the Independent Sample T-test. The results of the study show that there are significant differences between the financial performance of Islamic and conventional banking for CAR and BOPO ratios. Meanwhile NPL/NPF, ROE and LDR/FDR did not show a significant difference.